2021
DOI: 10.3390/antiox11010105
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Green Pea (Pisum sativum L.) Pods Extracts and Their Potential Exploitation as Ingredients in Nutraceutical Formulations

Abstract: Agro-industrial wastes contain a large number of important active compounds which can justify their use as innovative ingredients in nutraceutical products. This study aimed to provide a complete analysis of active molecules, namely (poly)phenols in pea pods water-based extracts, through a UHPLC-Q-Orbitrap HRMS methodology. Data showed that 5-caffeoylquinic acid, epicatechin, and hesperidin were the most relevant (poly)phenols found in the assayed extracts, with a mean value of 59.87, 29.46, and 19.94 mg/100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The total free radical scavenging activity of the red bean extracts was determined using the method reported in the literature with modifications [ 19 ]. Briefly, DPPH (4 mg) was solubilized in 10 mL of MeOH and then diluted to reach an absorbance value of 0.90 (±0.05) at 517 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The total free radical scavenging activity of the red bean extracts was determined using the method reported in the literature with modifications [ 19 ]. Briefly, DPPH (4 mg) was solubilized in 10 mL of MeOH and then diluted to reach an absorbance value of 0.90 (±0.05) at 517 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The TPC value found in the analyzed water-based extracts was lower than those reported by Hashemi et al [ 33 ], who obtained methanol-based extracts of broad bean hulls with Soxhlet, percolation, and ultrasound-assisted extraction, which reported TPC values ranging from 54 to 110 mg GAE/g. Moreover, in our previous investigation performed on the water-based extract of broad pea hulls [ 30 ], we reported that pea sample extracts showed a lower TPC value (9.7 vs. 8.2 mg/g). Furthermore, the two most significant compounds identified in the pea sample extracts were chlorogenic acid and epicatechin, with average values of 59.87 and 29.46 mg/100 g, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The total phenolic content (TPC) was determined following a previously published procedure [ 30 ]. In short, 125 µL of the Folin–Ciocalteu reagent (2 N) was added to 125 µL of sample and 0.5 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…Phytic acid is the main antinutrient in legumes (Castaldo et al., 2022; Ojo, 2021). As a strong chelating agent, it can form complexes with proteins and minerals (e.g., Ca, Fe, Zn, and Mg), and thus makes such nutrients unavailable, leading to micronutrient deficiencies (Y. Kumar et al., 2021; Ojo, 2021).…”
Section: Nutritional and Bioactive Propertiesmentioning
confidence: 99%